The Influence Of Work Allowances, Work Discipline, And Work Motivation On The Performance Of ASN PTUN Jakarta - David; Iwan Kurniawan Subagja; Dewi Rejeki (Indonesian Journal Economic Review (IJER), 2026)
To determine the Influence of Performance Allowance and Work Discipline on the Performance of Civil Servants of the Jakarta State Administrative Court Through Work Motivation. This study uses quantitative research with a descriptive approach. This research was conducted at the Jakarta State Administrative Court office on Jalan A. Sentra Primer Baru Timur, Pulo Gebang, East Jakarta City, DKI Jakarta Province. The population in this study was all Civil Servants at the Jakarta State Administrative Court, namely 57 respondents. The sample in this study was taken using a saturated sampling technique. The results are in the form of the Influence of Performance Allowance and Work Discipline on the Performance of Civil Servants of the Jakarta State Administrative Court Through Work Motivation.